Accentuated eccentric loading in lower-body resistance training: a systematic review of acute and chronic adaptations on strength, power, and speed outcomes - Zhong, Jinghui; Yu, Tongwu; Xiao, Yan; Wu, Hao (Frontiers in Physiology, 2026)
Background and ObjectivesAccentuated eccentric loading (AEL) prescribes an eccentric load exceeding the paired concentric load, exploiting the muscle’s greater force capacity during lengthening. Evidence suggests benefits, but findings on its acute and chronic efficacy versus traditional resistance training (TRT) remain inconsistent. Uncertainties persist regarding acute potentiation, optimal eccentric-to-concentric ratios, and transfer to sport performance. This review synthesises current evidence, distinguishing acute from chronic outcomes and summarising prescription variables to guide practice.MethodsThis review followed PRISMA 2020 guidelines. PubMed, Scopus, Web of Science, and Embase were searched to June 2025 for acute and chronic trials where eccentric loading exceeded concentric loading in lower limb exercises. We included peer-reviewed acute and longitudinal trials in healthy humans that (i) applied Accentuated eccentric loading to lower-body resistance or jump exercises, (ii) compared AEL with a traditional isoinertial or equal-load condition, and (iii) reported at least one outcome related to maximal strength, jump performance, sprint speed or change-of-direction ability. Data on study design, AEL configuration (eccentric and concentric loads, movement type, loading method, volume and frequency) and performance outcomes were extracted. Standardized effect sizes were taken from the original articles where reported and summarized qualitatively; no new meta-analytic pooling was performed due to heterogeneity in study designs and incomplete reporting.ResultsTwenty trials met the inclusion criteria. Acute studies showed that AEL enhanced explosive performance when eccentric intensity was set at 110%–120% of concentric one-repetition maximum (1RM) in back squats or when an additional 10%–30% of body mass was applied in dumbbell release jump drills. However, responses were variable, with very high loads or poor timing occasionally impairing performance. Chronic training programs reported maximal strength gains ranging from approximately 9%–22%, with jump height improvements between 4% and 11%. While these adaptations were generally superior or comparable to traditional training, the magnitude of transfer to sprint and COD performance was inconsistent. Certainty of evidence (GRADE) was moderate for strength outcomes due to consistent positive effects, but low to very low for speed outcomes due to imprecision and heterogeneity.ConclusionAEL is an effective method to enhance lower body maximal strength and explosive performance, particularly when applying 110%–120% 1RM in multi-joint lifts or adding 10%–30% body mass in jump drills. However, the transfer of these adaptations to sprint and change-of-direction speed remains uncertain. Due to the high heterogeneity of study protocols and small sample sizes, these findings should be interpreted with caution. Future research requires standardized reporting and larger randomized trials to optimize programming.